Characterization of Calcium-Dependent Protein Kinases 3, a Protein Involved in Growth of Cryptosporidium parvum - Zhang, Qiang; Guo, Yaqiong; Li, Na; Li, Yu; Su, Jiayuan; Xu, Rui; Zhang, Ziding; Feng, Yaoyu; Xiao, Lihua (Frontiers in Microbiology, 2020)
Calcium-dependent protein kinases (CDPKs) are considered promising targets for pharmaceutical intervention of cryptosporidiosis. Whole-genome sequencing has revealed the presence of several CDPKs (CpCDPKs) in C. parvum. In this study, we expressed recombinant CpCDPK3 encoded by the cgd5_820 gene in Escherichia coli. The biologic characteristics and functions of CpCDPK3 were examined using qRT-PCR, immunofluorescence microscopy and in vitro neutralization assay. The expression of the cgd5_820 gene peaked in merozoites during in vitro culture while the CpCDPK3 protein was expressed in both sporozoites and merozoites. Polyclonal antibodies against CpCDPK3 showed no significant inhibitory effects on host invasion by the parasites. We assessed the inhibitory effects of 46 candidate compounds from molecular docking of CpCDPK3 on both C. parvum development and CpCDPK3 enzyme activities. One compound was identified to be effective. Results of these analyses suggest that CpCDPK3 might play an important role in the growth of C. parvum.